Environmental Damage as Negative Externality: Uncertainty, Moral Complexity and the Limits of the Market - Laura Centemeri (e-cadernos ces)
The economic concept of negative externalities is the dominant frame in environmental policies. Revisiting environmental damage with a sociological approach, I show how the process of externalities definition and internalisation is a political process in which a public is constituted and common problems are collectively defined and addressed. In particular, I highlight the presence in this process of two kinds of uncertainty which have to be dealt with: epistemic uncertainty and moral uncertainty. Keeping these two forms of uncertainty analytically separated is useful in order to understand the limits of the market as a way to internalize environmental externalities and to analyse in their specificities the different types of translation, mediation and composition which are needed in order to create the conditions for a truly inclusive and democratic public deliberation on environmental damage and its reparation.